‘What’s done can’t be undone’: Verbal Contractions in Modern English. - Pacheco-Franco, Marta; Calle-Martín, Javier (My University, 2024)
The habit of contracting words originates in the intrinsic tendency of languages to assimilate the pronunciation of two neighbouring sounds. In Present-day English, this phenomenon is most plainly observed in the so-called ‘telescoped phrases’, a term that refers to all those cases of elision affecting auxiliary verbs, as exemplified by it’s and doesn’t (Peters, 2004, p. 126). Among these, there are, on the one hand, the contractions featured in operators, i.e., “the larger class containing the NICE [i.e. negation, inversion, code and emphasis] verbs in all their uses” (Huddleston & Pullum, 2002, p. 104n, our emphasis). In these cases, the element contracted is a verb, either in its functional or lexical uses, and the elision takes place at the beginning of the word, as in it’s for it is or they’ve for they have. On the other hand, the negative adverb not may also be contracted to n’t when it modifies an operator, thereby losing its mid-word vowel and its free-word status in the process. The examples doesn’t for does not and isn’t for is not illustrate this phenomenon, with the exception of the negative modal can’t, which stands for the univocal full form cannot. Today, contractions are typically employed in colloquial registers, whether they be spoken or written. However, it remains unclear when these structures first became widespread in the language and how they became an index of informal English.
Keywords: Inglés - Gramática; Inglés - Sintaxis; Early Modern English; Late Modern English; Contractions; Gender; Text types